Question Formation in || Gana, a Khoesan Language - M. Letsholor, Rose (Linguistique et Langues Africaines, 2016)
ǁGana is one of Botswana’s indigenous languages. It belongs to the Western branch of the Central Khoesan group of languages. Not much is known about the syntax of this language, which is now facing extinction. This paper makes a contribution towards documenting ǁGana by investigating question formation in this language. It specifically aims at answering to two questions, namely (a) What are the different question words that ǁGana uses to form content questions? and (b) What positions do these question words occupy in this language? Regarding question (a), I show that ǁGana has two basic forms used to produce content questions: máá ‑ and nùú and that a third form, hi‑, is used specifically in questions where the gender of the question personed is unknown. Máá‑ is the basic form corresponding to English argument question words ‘who’, ‘which’, ‘whose’ and ‘whom’ and it is also the basic form for the adjunct questions ‘where’, ‘how’ and ‘when’. Nùú is the basic form corresponding to ‘what’ and ‘why’. Regarding question (b), there are three main positions that question words can occupy in ǁGana: (i) sentence initial, (ii) after subject, and (iii) after a fronted object in transitive or ditransitive structures. An interesting finding is that question words never occur in sentence final position in ǁGana irrespective of whether the question word is an argument of the verb (subject, direct or indirect object) or an adjunct. This suggests that, in ǁGana, the sentence-final position is not a focus position given that question words are treated in the literature as focused constituents.